Pengembangan SDM dalam Mewujudkan Organisasi di Era Digital: Persfektif Hukum Ekonomi Islam pada Lembaga Pendidikan Tinggi - Nia Puspita Hapsari; Imam Muhtadin; Endang Ruswanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of the virtual website period even demands that organizations, including higher education institutions, under go transformation in human resource (HR) management to develop competitiveness, on an ongoing basis. The strategy of expanding human resources is considered as the key to forming individuals who are adaptive, competent, and have integrity in accordance with the principles of Islamic Economic Law. The study aims to examine the strategy ode developing human resources in higher education institutions in facing challenges of the virtual period based on the perspective of Islamic Economic Law. The method in the study is descriptive qualitative analysis. The results of the study found that effective human resources development needs to be integrated with digital competence, improving spiritual quality, and implementing sharia value such as justice, trust worth thinnest, and balance. The implication of the study present human resource policies that are adjusted to Islamic values, and remain relevant to the needs of the organizations.